PENERAPAN MEDIA POSTER BERBASIS INKUIRI DENGAN STRATEGI KOOPERATIF UNTUK MENINGKATKAN KECAKAPAN BERPIKIR RASIONAL SISWA SMP - Lalu Jinade; Abdul Wahab Jufri; Agus Ramdani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2013)
This study aims to determine the effect of the application of Inquiry-Based Media Poster (MPBI) with the cooperative strategies to improve rational thinking skills junior high school students. This study classified the type of quasi-experimental study (quasi-experimental research) with a pretest-posttest non-equivalent control group design ( 2x2x2 factorial ). The research instrument shaped test of rational thinking skills of students, in the form of a multiple choice test with every answer on the grounds. The data were analyzed by using SPSS Anacova technique 18 for Windows. The results showed that: 1) rational thinking skills that students learn to use MPBI and students learn to use drawing media different significantly; 2) rational thinking skills students learn through STAD cooperative strategies and student learning through NHT types did not different significantly; and 3) interaction between MPBI, cooperative strategy ( STAD and NHT ), and academic ability does not significantly affect rational thinking skills of students.